Photoluminescence, laser damage threshold, optical transmittance, FTIR, mechanical, dielectric, thermal and XRD studies on Bis – Glycine hydrochloride single crystal - Gobinathan, L.; Boopathy, K. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Single crystals of Bis – glycine hydrochloride (BGHC) were grown from aqueous solution by means of slow evaporation and slow cooling techniques. Single crystal XRD study reveals that the grown BGHC crystallizes in orthorhombic system with space group P212121 and the obtained unit cell parameters are a = 5.32 Å, b = 8.10 Å and c = 18.01 Å. Powder X – ray diffraction pattern of grown BGHC has been indexed. Functional groups present in the BGHC crystals were identified by FT – IR spectral analysis. The transmission and absorption spectra for the grown BGHC crystal shows that the lower cut off wavelength lies at 235 nm. The photoluminescence spectrum of the grown crystal was recorded. Mechanical hardness of the grown BGHC was determined and Vickers microhardness hardness number was calculated. Laser damage threshold study was carried out for the grown crystal using Nd:YAG laser. The thermal stability of the grown crystal was investigated using thermogravimetric analysis and the grown crystal is thermally stable up to 198 °C. Particle size dependent second harmonic generation efficiency of the grown crystal was examined by Kurtz and Perry powder technique using 1064 nm laser.